Allowance for School Graduate Practice Performance in Slovakia: Impact Evaluation of the Intervention - Lucia Svabova; Katarina Kramarova (Mathematics, 2022)
This study aims to evaluate the impact of a selected active labour market policy measure that has been applied in Slovakia—Allowance for school graduate practice performance—on the employability of young jobseekers and their sustainability in the labour market, and thus, it will also empirically contribute to the field of relevant literature. The policy targets unemployed school graduates, and it enables them to acquire professional skills and practical experience that corresponds with their level of education, work habits, and possible direct contact with potential employers. At the same time, this measure addresses a long-standing gap in the Slovakian education system, namely, the insufficient linkages between the educational process, the practices in the field, and the requirements of the labour market. Using fiscal resources to finance this policy, it provides a natural and logical platform to investigate the relevance of the outcome of this measure in the context of its proclaimed objectives. In light of this, we employed a counterfactual approach to compare the results of the participants who were affected the measure (recipients; treated group) and non-participants, as their counterparts (comparison/control group), using an instrumental variable to mitigate self-selection and selection-bias problems. Our findings show that this policy intervention has a short- or medium-term impact on the employability of unemployed school graduates and the sustainability of their careers. In addition, a positive impact on their monthly wages was observed. We also came to the conclusion that, assuming the measure is linked to other labour market policy interventions, which is aimed at employers that are willing to hire young unemployed people, it would be possible to improve the functionality and effectiveness of support for the unemployed through indirect measures.